ҚОРАКЎЛ СОВЛИҚЛАРИ КЎПАЙИШ СИФАТИНИНГ СЕМИЗЛИК ДАРАЖАСИ БИЛАН БОҒЛИҚЛИГИ - Базаров, Б.М.; Сиддиқов, М.Р. (SCIENCE and SOCIETY, 2020)
The article studied the influence of fatness of Karakul queens on the rate of fertilization. The intensity of coming to hunting in queens with overweight fatness was revealed.